Antarctic Ice Mass Change (2003–2016) Jointly Estimated by Satellite Gravimetry and Altimetry. Issue 9 (8th September 2022) - Kim, Byeong‐Hoon; Seo, Ki‐Weon; Lee, Choon‐Ki; Kim, Jae‐Seung; Chen, Jianli; Wilson, Clark R.
Abstract: Accurate estimation of ongoing Antarctic ice mass change is important to predict future ice mass loss and subsequent sea level rise. Over the past two decades, Antarctic ice mass changes have been observed by the gravity recovery and climate experiment (GRACE) gravity mission, but the low spatial resolution of GRACE has limited understanding of glacial‐scale contributions. In this study, we combine GRACE and altimetry data to obtain mass change estimates with greatly improved spatial resolution. Combined estimates are obtained by a constrained linear deconvolution algorithm used in a previous GRACE study. Satellite altimetry observations are introduced as an a priori and resulting estimates retain the high spatial resolution of satellite altimetry, but when smoothed agree with low resolution GRACE data. These glacial‐scale estimates also agree with ice budget calculations using the input‐output method. Plain Language Summary: Previous observations of Antarctic ice mass change from the gravity recovery and climate experiment (GRACE) satellite have limited the investigation of small‐scale changes because GRACE cannot distinguish signals smaller than a few hundred km. In this study, we improved the spatial resolution of GRACE mass change estimates by incorporating observations from altimetry satellites. Our new ice mass change estimates are similar to previous GRACE results at a continental scale but provide higher spatial resolution over Antarctic glaciers. These new estimates agree with glacier mass change predictions from an independent method. Key Points: We estimated high‐resolution (∼27 km) Antarctic ice sheet (AIS) mass balances using gravity recovery and climate experiment (GRACE) and satellite altimetry data Our estimates effectively reduce spatial leakage in GRACE observation and uncertainty in altimetry observation Our new estimates agree well with glacial‐scale ice mass balances from the input‐output method